2015
DOI: 10.1007/s10096-015-2319-8
|View full text |Cite
|
Sign up to set email alerts
|

High medical impact of implementing the new polymeric bead-based BacT/ALERT® FAPlus and FNPlus blood culture bottles in standard care

Abstract: Blood culture (BC) efficiency is critical for the diagnosis of bloodstream infection (BSI). We evaluated the impact on standard care of implementing the new BacT/ALERT® FAPlus and FNPlus BC bottles containing antibiotic-binding polymeric beads. We measured positivity rates and time to detection (TTD) during the first 10 months of implementation (PF) and during the previous 10-month period (PS) during which we were using standard aerobic (SA) or standard anaerobic (SN) BC bottles. For each period, the same numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The BacT/Alert system has been produced with bottles containing resins instead of activated carbon, and studies that have been performed to compare the performance of these two media indicate that the adsorption of antibiotics by resins is higher than that of activated carbon, with an increased recovery rate and shorter TTD (Mitteregger et al, 2013; Doern et al, 2014; Fiori et al, 2014; Kirn et al, 2014). However, in terms the positive detection rate within 12 h of culture, resins were found to have no advantage over the standard bottles containing activated carbon (Amarsy-Guerle et al, 2015). Fiori et al demonstrated that the BACTEC system showed a better recovery rate for gram-negative bacteria, whereas the BacT/Alert resin bottles showed a higher detection rate for gram-positive bacteria (Fiori et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The BacT/Alert system has been produced with bottles containing resins instead of activated carbon, and studies that have been performed to compare the performance of these two media indicate that the adsorption of antibiotics by resins is higher than that of activated carbon, with an increased recovery rate and shorter TTD (Mitteregger et al, 2013; Doern et al, 2014; Fiori et al, 2014; Kirn et al, 2014). However, in terms the positive detection rate within 12 h of culture, resins were found to have no advantage over the standard bottles containing activated carbon (Amarsy-Guerle et al, 2015). Fiori et al demonstrated that the BACTEC system showed a better recovery rate for gram-negative bacteria, whereas the BacT/Alert resin bottles showed a higher detection rate for gram-positive bacteria (Fiori et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Variables affecting blood culture yields include the volume of blood cultured, the number of cultures performed, the culture media used, the detection methods, and the length of incubation (3). Media containing polymeric beads that adsorb antimicrobials, such as BacT/Alert FA Plus (aerobic) and FN Plus (anaerobic) media, have been shown to provide improved recovery and early detection of microorganisms compared with charcoal-containing BacT/Alert FA and FN media (4), with shorter detection times (5). …”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to the improved binding kinetics of the resin-based media for a variety of antimicrobial agents [19]. Based on these results, the resin-based medias, including the FAN Plus media, have been thoroughly evaluated for culturing of blood and several types of sterile body fluids [20][21][22][23][24]. However, the utility of this method had not previously been evaluated for PD effluent culture.…”
Section: Discussionmentioning
confidence: 99%